PENERAPAN KURIKULUM HOLISTIK DALAM MENINGKATKAN KESEIMBANGAN ANTARA PENGETAHUAN, KETERAMPILAN, DAN SIKAP - Isnaliati, Isnaliati; Azhar, Asmanuddin; Novikasari, Novikasari; Tumaleno, Sri Wulandari (Jurnal Sultra Elementary School, 2024)
Holistic curriculum is an educational approach that aims to integrate aspects of knowledge, skills, and attitudes in a balanced way in the learning process. This article discusses the basic concept of holistic curriculum, its implementation in various educational contexts, and its influence on the formation of whole learners. This study uses a literature study method by analyzing data from various reliable sources. The results of the study indicate that the implementation of a holistic curriculum can increase student engagement, develop life skills, and form strong characters. However, its implementation requires support from all stakeholders, including educators, parents, and policy makers.